Digital Transformation Effects on Accounting and Auditing Functions (gjstudies, 2017)
This research investigates the multifaceted effects of digital transformation on accounting and auditing functions through a novel methodological framework that combines computational linguistics, process mining, and institutional theory. Unlike previous studies that focus primarily on technological adoption, this paper examines thecognitive, procedural, and institutional shifts occurring within accounting and auditingpractices as they adapt to digital environments. We introduce the concept of ’digitalhermeneutics’ in accounting—the interpretive processes by which accounting professionals make sense of digital data streams—and develop a framework for analyzinghow digital transformation reconfigures traditional accounting epistemologies. Ourmethodology employs a mixed-methods approach combining automated text analysisof accounting standards revisions from 1995-2005, process mining of audit trails fromearly enterprise resource planning systems, and ethnographic case studies of accountingdepartments undergoing digital transitions. The results reveal three distinct patternsof transformation: (1) a shift from periodic to continuous accounting processes enabledby real-time data flows, (2) the emergence of ’algorithmic judgment’ in auditing wherehuman expertise increasingly interfaces with automated analysis systems, and (3) thedevelopment of new forms of accounting materiality that account for digital assets andintangible value flows. Our findings demonstrate that digital transformation is notmerely a technological overlay on existing practices but fundamentally reconfiguresthe epistemological foundations of accounting and auditing. The research contributesoriginal insights into how digital technologies are reshaping the very nature of financialrepresentation, verification, and accountability, with implications for accounting education, standard-setting, and professional development in the emerging digital economy.